Potential association between obstructive lung diseases and cognitive decline - Figat, Magdalena; Wiśniewska, Aleksandra; Plichta, Jacek; Miłkowska-Dymanowska, Joanna; Majewski, Sebastian; Karbownik, Michał S.; Kuna, Piotr; Panek, Michał G. (Frontiers in Immunology, 2024)
Introduction: Chronic obstructive lung diseases, such as asthma and COPD, appear to have a more extensive impact on overall functioning than previously believed. The latest data from clinical trials suggests a potential link between cognitive deterioration and chronic obstructive inflammatory lung disease. This raises the question of whether these diseases affect cognitive functions and whether any relevant biomarker may be identified.Methods: This prospective observational study included 78 patients divided equally into asthma, COPD, and control groups (n=26, 27 and 25 respectively). The participants underwent identical examinations at the beginning of the study and after at least 12 months. The test battery comprised 16 questionnaires (11 self-rated, 5 observer-rated, assessing cognition and mental state), spirometry, and blood samples taken for PKA and CREB mRNA evaluation.Results: A 2.3-fold increase in CREB mRNA was observed between examinations (p=0.014) for all participants; no distinctions were observed between the asthma, COPD, and control groups. Pooled, adjusted data revealed a borderline interaction between diagnosis and CREB expression in predicting MMSE (p=0.055) in COPD, CREB expression is also associated with MMSE (=0.273, p=0.034) like with the other conducted tests (=0.327, p=0.024) from COPD patients.No correlations were generally found for PKA, although one significant negative correlation was found between the first and second time points in the COPD group (=-0.4157, p=0.049,).. Discussion: Chronic obstructive lung diseases, such as asthma and COPD, may have some linkage to impairment of cognitive functions. However, the noted rise in CREB mRNA expression might suggest a potential avenue for assessing possible changes in cognition, especially in COPD; such findings may reveal additional transcription factors linked to cognitive decline.